Clinical, Pathological and Immunohistochemical Effects of Arsenical-Ferruginous SPA Waters on Mild-To-Moderate Psoriatic Lesions: A Randomized Placebo-Controlled Study. (April 2013) - Borroni, G.; Brazzelli, V.; Fornara, L.; Rosso, R.; Paulli, M.; Tinelli, C.; Ciocca, O.
Thermalism and spa treatments are traditionally considered effective in a number of dermatologic inflammatory conditions, yet there is scarce evidence about spring water effectiveness on psoriasis in a daily setting. We enrolled 34 patients with mild-to-moderate psoriasis in a double-blind, randomized, placebo-contralaterally-controlled trial, to evaluate Levico and Vetriolo arsenical-ferruginous water effectiveness on psoriatic lesions by daily 20-minute wet packing for 12 consecutive days. Clinical, histopathologic and immunohistochemical parameters were considered. A statistically significant difference between spa water-treated lesions and placebo-treated lesions in the same patients was demonstrated for histopathologic and immunohistochemical parameters. Since iron ions have an antiproliferative effect on epithelia, and magnesium ions have an anti-inflammatory effect, Levico and Vetriolo water effectiveness on psoriasis could be addressed to their content of these ions.